Early metabolic responses to lithium/pilocarpine‐induced status epilepticus in rat brain. (8th October 2015) - Imran, Imran; Hillert, Markus H.; Klein, Jochen
Abstract: The lithium–pilocarpine model of status epilepticus is a well‐known animal model of temporal lobe epilepsy. We combined this model with in vivo microdialysis to investigate energy metabolites and acute cellular membrane damage during seizure development. Rats were implanted with dialysis probes and pretreated with lithium chloride (127 mg/kg i.p.). Twenty‐four hours later, they received pilocarpine (30 mg/kg s.c.) which initiated seizures within 30 min. In the dialysate from rat hippocampus, we observed a transient increase in glucose and a prominent, five‐fold increase in lactate during seizures. Lactate release was because of neuronal activation as it was strongly reduced by infusion of tetrodotoxin, administration of atropine or when seizures were terminated by diazepam or ketamine. In ex vivo assays, mitochondrial function as measured by respirometry was not affected by 90 min of seizures. Extracellular levels of choline, however, increased two‐fold and glycerol levels 10‐fold, which indicate cellular phospholipid breakdown during seizures. Within 60 min of pilocarpine administration, hydroxylation of salicylate increased two‐fold and formation of isoprostanes 20‐fold, revealing significant oxidative stress in hippocampal tissue. Increases in lactate, glycerol and isoprostanes were abrogated, and increases in choline were completely prevented, when hippocampal probes were perfused with calcium‐free solution. Similarly, administration of pregabalin (100 mg/kg i.p.), a calcium channel ligand, 15 min prior to pilocarpine strongly attenuated parameters of membrane damage and oxidative stress. We conclude that seizure development in a rat model of status epilepticus is accompanied by increases in extracellular lactate, choline and glycerol, and by oxidative stress, while mitochondrial function remains intact for at least 90 min. Membrane damage depends on calcium influx and can be prevented by treatment with pregabalin. Status epilepticus (SE) was induced in rats by lithium–pilocarpine ('Pilo') administration, and extracellular metabolites were measured by microdialysis. Seizures caused several‐fold increases in lactate levels which were attenuated by diazepam ('Diaz'), ketamine, atropine and tetrodotoxin (TTX). Indicators of oxidative stress and membrane damage were also increased during seizures. Omission of calcium and pregabalin, a calcium channel blocker, reduced cellular damage induced by SE. Abstract : Status epilepticus (SE) was induced in rats by lithium–pilocarpine ('Pilo') administration, and extracellular metabolites were measured by microdialysis. Seizures caused several‐fold increases in lactate levels which were attenuated by diazepam ('Diaz'), ketamine, atropine and tetrodotoxin (TTX). Indicators of oxidative stress and membrane damage were also increased during seizures. Omission of calcium and pregabalin, a calcium channel blocker, reduced cellular damage induced by SE.